ELEMENTARY SCHOOL TEACHERS USE VIDEO TUTORIALS AND GOOGLE FORMS AS ALTERNATIVES TO ONLINE LEARNING MATERIALS - Hidayah, Muslihatul; Emilda, Emilda; Katarina, Dona; Rahadyan, Andri (Universitas Muhammadiyah Mataram, 2021)
Abstract: Â Teachers are still struggling to create and use online learning media in teaching and learning activities in the current pandemic environment, causing partner issues. Teachers are still working to convey the material fascinating in mathematics and natural sciences. Easily understood by students, such as learning videos; a lack of learning media owned by teachers and schools for learning development, such as creating quizzes or assignments; and a lack of training in making alternative distance learning media provided to teachers. The aim is to improve elementary school teachers' skills in creating video tutorials and using Google Forms to increase the quality of online learning. Methods of implementation are socialization and training. SDN Cimanggis 01 Bojonggede is the partner of this community service. There are 12 participants. For monitoring and evaluation, participants fill out the respondent's questionnaire. The results are that 80 percent of participants can create video tutorials using OBS and use Google Forms.